2015
DOI: 10.2174/1570162x13666150407143838
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Adherence Factors Associated with Viral Load Suppression in HIV-Infected Adults Initiating Therapy in Northern Nigeria: A Randomized Controlled Trial of a Peer Support Intervention

Abstract: High levels of viral suppression and low prevalence of drug resistance mutations (DRMs) were seen in this cohort participating in an ART adherence study in Northern Nigeria. Self-reported good adherence and optimal Rx refill rates were reported as significant predictors of VL suppression. Our findings indicate that ART adherence will improve significantly regardless of whether HIV-infected adults received peer-education-based medication adherence interventions or standard of care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…These interventions included adherence support provided by lay health workers or volunteers, community- and facility-based adherence activities, home-based directly observed therapy (DOT) or adherence support by lay treatment supporters, and community-based social support. Two studies were conducted among both adults and adolescents [ 82 , 83 ]; the remaining 11 were conducted among adults [ 40 , 41 , 76 81 , 84 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These interventions included adherence support provided by lay health workers or volunteers, community- and facility-based adherence activities, home-based directly observed therapy (DOT) or adherence support by lay treatment supporters, and community-based social support. Two studies were conducted among both adults and adolescents [ 82 , 83 ]; the remaining 11 were conducted among adults [ 40 , 41 , 76 81 , 84 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (three RCTs, two quasi-experimental studies, and one prospective and two retrospective cohort studies) tested or examined associations between adherence outcomes and community-based adherence support (CBAS) interventions [ 76 83 ]. Six studies were conducted among adults [ 76 81 ] and two included adults and adolescents [ 82 , 83 ]. CBAS interventions included adherence support through home visits by a community-based health worker or volunteer and included activities such as DOT, basic clinical assessments, referrals, pill counts, and home ART delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Males were at risk of attrition in the prior evaluation but were not at risk in the current evaluation. Several studies have consistently showed males at high risk of attrition due to several reasons, including employment related constraints and poor health seeking behaviour leading to late presentation [13,15,38,39]. During the study period the country did not implement many specific interventions that targeted men.…”
Section: Discussionmentioning
confidence: 99%
“…Group support also has a positive effect on HIV patient compliance, this is supported by interactions between peer support group members, this is supported by previous research that 89.9% of peer support helps HIV patients in sharing and increasing knowledge and experience regarding the importance of taking drugs with sustained effect. The statement in question is that activities in peer support should not be stopped, because if stopped will have a role in the psychosocial of HIV patients, so that it can affect the ARV treatment process [21][22][23][24]. This statement can also be linked to the analysis of education in this study that education has no significant difference, because education itself has a short effect compared to interactions with peer support [25].…”
Section: Discussionmentioning
confidence: 96%